PERANCANGAN SISTEM BIMBINGAN KONSELING UNTUK PENANGANAN PELANGGARAN SISWA DI SMP ISLAM AL ABIDIN SURAKARTA BERBASIS WEB - Murniyati Murniyati; Agustina Srirahayu (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2022)
Guidance Counseling in a school is an effort to help students in the process of completing studies properly, knowing in detail the potential of students and planning their future self-development. It is the duty of the school to provide good services and facilities in all aspects including the activities of the Counseling Guidance for students. Counseling counseling in schools will be effective if there is a supporting information system. Therefore it is necessary to build a system that handles the Guidance and Counseling process starting from planning, managing student data, recording violations and problems, scheduling guidance to reporting to parents.